Evaluation of potentially inappropriate prescribing and deprescription as elements of good medical practice in elderly patient care - Susło, Anna; Horoch-Łyszczarek, Ewa; Pochybełko, Ewa; Mizia, Sylwia (Family Medicine & Primary Care Review, 2023)
The ongoing increase in the proportion of elderly people in society, sometimes referred to as the aging societies phenomenon, has numerous effects. Multimorbidity affects about every third person in the general population and, on average, the likelihood of chronic illness increases with age, so multimorbidity is more common in older age groups. This increases the demand for medication, leading to concurrent use of many drugs, which is referred to as polypharmacy. We carried out a literature review to identify the problems associated with the use of medications in people sixty years and older. Aging societies contain an increasing number of elderly people struggling with the burden of multimorbidity and the resulting polypharmacy. They require a systemic approach to prescription problems, which include potentially inappropriate medication (PIM) and overprescription, as well as potential prescribing omission (PPO), taking into account issues like lack of patient compliance and self-medication. Any attempt to solve these problems requires tools to objectively evaluate prescription practice, using the existing and emerging capabilities of electronic health records (EHR), actively encouraging all medical personnel who prescribe medications or evaluate their use (including physicians, nurses and pharmacists) to join rational deprescribing attempts, and convincing patients that more drugs are not always better.